Reviews and syntheses: Current perspectives on biosphere research 2024–2025 – eight findings from ecology, sociology, and economics - F. J. Bohn; F. J. Bohn; A. Bastos; R. Martin; A. Rammig; N. S. Koh; G. B. Sioen; G. B. Sioen; B. Buscher; L. Carver; F. DeClerck; M. Drupp; et al. (Biogeosciences)
This review of recent advances in biosphere research aims to provide information on eight selected themes related to changes in biodiversity, ecosystem functioning, social and economic interactions with ecosystems, and the impacts of climate change on the biosphere. An interdisciplinary panel of experts selected these eight themes from a public survey based on relevance and scientific evidence that have the potential to guide future actions as well as inspire future research questions. Our focus is on the interactions between climate, biosphere, and society and on strategies to sustain, restore, or promote ecosystems and their services. The themes focus on innovative opportunities for coastal habitats, forest linkages to droughts, and increasing fire risks. We further discuss nature-based carbon dioxide removal (CDR) implementation risks and the share of (semi-)natural habitats in the landscape. Finally, we highlight the importance of comprehensive international policy packages and the social–economic value of ecosystems in the future and present the idea of convivial conservation. Based on an analysis of these eight topics, we have synthesized four overarching insights: (i) improve mechanisms of inclusive decision-making, (ii) establish and strengthen incentives for sustainable practices, (iii) measure and share regional features, and finally (iv) adopt long-lasting holistic landscape management strategies. This review emphasizes that the interlinked challenges for ecosystems, including the socio-economic dimensions, require interdisciplinary and integrative approaches to develop effective and sustainable solutions.